Molecular epidemiology of Klebsiella pneumoniae strains that produce SHV-4 beta-lactamase and which were isolated in 14 French hospitals. - Arlet, G (1994)
Preliminary results suggested that the diffusion in France of the SHV-4 extended-spectrum beta-lactamase was probably due to the spread of one single epidemic strain of Klebsiella pneumoniae. In this study, we tested various phenotypic and genotypic markers to compare K. pneumoniae strains producing this enzyme isolated in 14 French hospitals between 1987 and 1989. All of the strains were of the same capsule serotype, K25. Twelve of them were of the same biotype: weak urease activity and no sucrose fermentation. Among the six plasmid profiles observed, one accounted for eight strains. Large plasmids of 170 kb encoding SHV-4 beta-lactamase were present in all strains of K. pneumoniae and could be transferred by conjugation with high frequency to Escherichia coli J53-2 or HB101 from all except one strain. Plasmid EcoRI restriction patterns suggested that these plasmids were closely related and similar to pUD18 encoding SHV-3 beta-lactamase, originally described in France and differing from SHV-4 by one amino acid substitution. Ribotyping with EcoRI and HindIII and genomic fingerprinting with XbaI by pulsed-field gel electrophoresis were concordant and suggested that 12 of the isolates recovered from the 14 hospitals were probably the same strain. Dissemination in France of the SHV-4 extended-spectrum beta-lactamase was thus essentially due to the diffusion of a single K. pneumoniae clone.